Audit of outcome of an extracapsular cataract extraction and posterior chamber intraocular lens training course. Issue 8 (1st August 2000) - Alhassan, Mahmoud B; Kyari, Fatima; Achi, Ibrahim B; Ozemela, Chinenyem P; Abiose, Adenike
Abstract : BACKGROUND: A training course for cataract surgery with intraocular lens implantation was organised in April 1997 at the National Eye Centre, Kaduna, Nigeria. Operations were performed by six Nigerian consultant ophthalmologists under the supervision of two surgeons from Aravind Eye Hospital, India. METHODS: A total of 175 eyes with uncomplicated cataracts were operated on after careful selection. All but six patients had extracapsular cataract extraction with posterior chamber intraocular lens insertion during the training programme. RESULTS: The mean age of the patients at operation was 54.2 years. One hundred and forty five of the operated eyes (85.8%) were blind before surgery of which six (3.6%) remained blind postoperatively. An uncorrected visual acuity of 6/60 or better was achieved in 87.3% eyes after surgery. Forty one patients (24.3%) were blind before surgery, two of whom (1.2%) remained blind afterwards. The most common intraoperative complication was posterior capsular rent which occurred in 10 eyes (5.7%); striate keratopathy/corneal oedema and cortical remnant were the most common immediate postoperative complications, occurring in 44.6% and 8.0%, respectively. CONCLUSION: With adequate surgical skills, extracapsular cataract extraction with posterior chamber intraocular lens implantation offers good visual rehabilitation even under training conditions.